Clinical, paraclinical, therapeutic features of acute decompensated heart failure in a Moroccan population - Meryem Haboub; Asmaa Mounssif; Mohamed Khaldi; Hanane Mechal; Abdenasser Drighil; Rachida Habbal (Scientific Reports)
Abstract Acute decompensated heart failure (ADHF) is a major health challenge globally, with high morbidity and mortality. Data from North African populations remain limited. This study aims to describe the clinical profile, precipitating factors, management, and short-term outcomes of patients admitted with ADHF to a tertiary care center in Morocco. We conducted a retrospective study of 138 Moroccan patients admitted with ADHF at Ibn Rochd University Hospital, Casablanca, between 2017 and 2019. Clinical, paraclinical, therapeutic features, and outcomes were analyzed. The mean patient age was 60.45 ± 15.77 years, with a male-to-female ratio of 1.6. Common risk factors included hypertension (36.2%), diabetes (28.3%), and smoking (37.7%). Prior cardiovascular disease was observed in 45.7%, and 32.6% had previous ADHF hospitalizations. On admission, 65.9% were in NYHA class III. The main precipitating factor was bronchopulmonary infection (35.5%). Ischemic heart disease (43.4%) was the leading etiology. Reduced LVEF was seen in 56.5%, HFmrEF in 20.3%, and HFpEF in 23.2%. Cardiogenic shock (10.9%), COPD (9.4%), and renal dysfunction were significant mortality predictors. Beta-blockers were restarted within five days in 33.3%. Clinical improvement occurred in 69.6% of patients; in-hospital mortality was 18.1%. ADHF in Moroccan patients presents at a younger age, with ischemic heart disease as the leading cause. Early intervention, improved adherence, and systemic healthcare strategies are essential.